IMMU-17. PEPTIDE VACCINE IMMUNOTHERAPY BIOMARKERS AND RESPONSE PATTERNS IN PEDIATRIC GLIOMAS. (5th November 2018) - Mueller, Soeren; Agnihotri, Sameer; Shoger, Karsen; Myers, Max; Villanueva, Clarence; Diaz, Aaron; Okada, Hideho; Pollack, Ian; Kohanbash, Gary
Abstract: Low-grade gliomas (LGGs) are the most common brain tumor affecting children. We recently reported an early phase clinical trial of a peptide-based vaccine, which elicited consistent antigen-specific T cell responses in pediatric LGG patients. Additionally, we observed radiologic responses of stable disease (SD), partial response (PR), and near-complete/complete response (CR) following therapy. To identify biomarkers of clinical response in peripheral blood, we performed RNA sequencing on PBMC samples collected at multiple time points. Patients who showed CR demonstrated elevated levels of T cell activation markers, accompanied by a cytotoxic T cell response shortly after treatment initiation. At week 34, patients with CR demonstrated both IFN signaling and Poly-IC:LC adjuvant response patterns. Patients with PR demonstrated a unique, late monocyte response signature. Interestingly, HLA-V expression, before or during therapy, and an early monocytic hematopoietic response were strongly associated with SD. Low IDO1 and PD-L1 expression before treatment and early elevated levels of T cell activation markers were associated with prolonged progression-free survival. Furthermore, we identified that genes associated with dendritic cell activation of T-cells correlated with IFNγ ELISPOT counts. Currently we are validating the observed response patterns and biomarkers in high-grade glioma patients treated with peptide vaccine immunotherapy. Overall, our data support the presence of unique peripheral immune patterns in LGG patients associated with different radiographic responses to our peptide vaccine immunotherapy. Future clinical trials, including our ongoing phase II LGG vaccine immunotherapy, should monitor these response patterns.